KADAR GLUKOSA, ALKOHOL DAN CITARASA TAPE ONGGOK BERDASARKAN LAMA FERMENTASI - Nurul Fahmi; Nurrahman - (Universitas Muhammadiyah Semarang, 2011)
Cassava starch industry is a byproduct solids derived from the extraction unit still contains a lot of carbohydrates to allow the tape to be made. Fermentation time required in the process of fermentation is 2-3 days, the appropriate time we will get a sense of tape that tastes a little sour and sweet with the scent of alcohol. The research objective was to determine levels of glucose, alcohol and flavour based on tape cassava fermentation time (0 days, 1 day, 2 days, 3 days, and 4 days). The results: significantly effect of fermentation duration on glucose, alcohol and organoleptic properties (fragrance, flavor, texture), whereas not significantly for color. Glucose and alcohol consentration on 3 days fermentation are 3.83 g% and 3.40% w/w, respectively. The best hedonic value on 3 days fermentation duration is 4.24 hedonic scale with criteria liked.